2014
DOI: 10.1021/ja5030657
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Allosteric Response as an Unprecedented Mechanism of Resistance to Antibiotics

Abstract: Ceftaroline, a recently approved β-lactam antibiotic for treatment of infections by methicillin-resistant Staphylococcus aureus (MRSA), is able to inhibit penicillin-binding protein 2a (PBP2a) by triggering an allosteric conformational change that leads to the opening of the active site. The opened active site is now vulnerable to inhibition by a second molecule of ceftaroline, an event that impairs cell-wall biosynthesis and leads to bacterial death. The triggering of the allosteric effect takes place by bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 24 publications
2
73
0
2
Order By: Relevance
“…It would be interesting to study the effect of such changes in the PBP2a on resistance to fifth-generation cephalosporins, especially because some of them are located in the non-penicillin-binding protein domain. Mutations in this part of PBP2a have already been reported as causing allosteric changes, conferring resistance to ceftaroline through an alteration of the salt bridge network at the allosteric site, thereby deteriorating the access of a second ceftaroline molecule to the active site (Fishovitz et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It would be interesting to study the effect of such changes in the PBP2a on resistance to fifth-generation cephalosporins, especially because some of them are located in the non-penicillin-binding protein domain. Mutations in this part of PBP2a have already been reported as causing allosteric changes, conferring resistance to ceftaroline through an alteration of the salt bridge network at the allosteric site, thereby deteriorating the access of a second ceftaroline molecule to the active site (Fishovitz et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…However, ceftaroline and ceftobiprole, new cephalosporin molecules recently introduced and approved for the treatment of community-acquired pneumonia and complicated skin and soft tissue infections, are active against MRS. Ceftaroline causes an allosteric change of PBP2a so that a second molecule can bind to the newly exposed active site (Fishovitz et al, 2014) and ceftobiprole can access the active site of PBP2a through its residue R2 (Chan et al, 2015). In spite of these developments, mecA gene is still at the centre of interest for the scientific community because of recent reports on ceftaroline-and ceftobiprole-resistant MRSA isolates, mainly due to mutations in mecA (Chan et al, 2015;Schaumburg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…By kinetic studies and by X‐ray crystallography of the mutants, Mobashery, Hermoso et al. were able to rationalize that the clinically observed mutations interfere with triggering of the allosteric signal by ceftaroline along the interacting amino acid network between the two sites 148, 150. These mutations allow the mutant variants of PBP2a to manifest resistance to ceftaroline by two different mechanisms: the first is a modest increase in the dissociation constant for ceftaroline binding to the allosteric site, and the second is disruption of the transmission of conformational changes necessary for opening the active site.…”
Section: Cell Wall Synthesis Inhibitorsmentioning
confidence: 99%
“…A recent study has proposed a novel resistance mechanism to explain the observed non-penicillin-binding domain changes and their impact on ceftaroline susceptibility. The hypothesis claims a disruption of an allosteric trigger by the mutations in PBP2a, affecting the ability (2) MSSA (33) 1 (3.0) 10 (33.3) 22 (100) MRSA (28) 0 (0) 0 (0) 1 (3.6) 11 (42.9) 9 (75.0) 7 (100) Chile (3) MSSA (93) (2) MSSA ( of ceftaroline to bind within the functional pocket (35). However, other studies have demonstrated no impact of ceftaroline inhibition in purified protein containing non-penicillin-binding domain changes (33).…”
mentioning
confidence: 99%